Accuracy Evaluation of Collapsed Cone Convolution and Monte Carlo Dose Calculation Algorithms for Helical Tomotherapy Planning and Volumetric Modulated Arc Therapy Planning in a Thorax Phantom - Kosiyaporn, Parinee; Klunklin, Pitchayaponne; Wanwilairat, Somsak (Princess of Naradhiwas University Journal, 2021)
The accuracy of the radiation dose delivery to the tumor and organ at risk depends on the radiation dose calculation algorithm. This study evaluated the photon dose calculation accuracy of the Collapsed cone convolution for Helical tomotherapy planning and the Monte Carlo algorithm for the Volumetric modulated arc therapy planning. The computational results of the two algorithms were compared with the radiation dose measurements in a heterogeneity thorax phantom. In the experiment, the Helical tomotherapy plan and the Volumetric modulated arc therapy were planned. The three lesions of lung cancer in the thorax phantom were single lung lesion, multiple lung lesions and single mediastinal lesion. Then a two-step verification was performed. The first step, the points dose were measured with an ionization chambers and the second step the dose distribution were measured with a cylindrical diode array detectors (ArcCHECK). The results of the points dose verification showed that the mean different between measurement and calculation dose of the Collapsed cone convolution algorithm and the Monte Carlo algorithm were 4.14% (-0.25% to -5.63%) and 1.11% (0.87% to -1.81%), respectively, with statistically significant differences. For the verification of the radiation dose distribution at the 3% -3 mm gamma index threshold, it was found that the Collapsed cone algorithm and the Monte Carlo algorithm gamma passing rate were 95.8% and 99.9%, respectively, with no statistically significant difference. The results of this study showed that there was no statistically significant difference of the dose distribution calculation accuracy in a heterogeneity medium between the Monte Carlo algorithm and the Collapsed cone convolution algorithm. However, the points dose calculation of the Monte Carlo algorithm was significantly more accurate than the Collapsed convolution algorithm.